Longitudinal analysis of ANA in the Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort. Issue 8 (25th March 2022) - Choi, May Yee; Clarke, Ann Elaine; Urowitz, Murray; Hanly, John; St-Pierre, Yvan; Gordon, Caroline; Bae, Sang-Cheol; Romero-Diaz, Juanita; Sanchez-Guerrero, Jorge; Bernatsky, Sasha; Wallace, Daniel J; Isenberg, David; et al.
Abstract : Objectives: A perception derived from cross-sectional studies of small systemic lupus erythematosus (SLE) cohorts is that there is a marked discrepancy between antinuclear antibody (ANA) assays, which impacts on clinicians' approach to diagnosis and follow-up. We compared three ANA assays in a longitudinal analysis of a large international incident SLE cohort retested regularly and followed for 5 years. Methods: Demographic, clinical and serological data was from 805 SLE patients at enrolment, year 3 and 5. Two HEp-2 indirect immunofluorescence assays (IFA1, IFA2), an ANA ELISA, and SLE-related autoantibodies were performed in one laboratory. Frequencies of positivity, titres or absorbance units (AU), and IFA patterns were compared using McNemar, Wilcoxon and kappa statistics, respectively. Results: At enrolment, ANA positivity (≥1:80) was 96.1% by IFA1 (median titre 1:1280 (IQR 1:640–1:5120)), 98.3% by IFA2 (1:2560 (IQR 1:640–1:5120)) and 96.6% by ELISA (176.3 AU (IQR 106.4 AU–203.5 AU)). At least one ANA assay was positive for 99.6% of patients at enrolment. At year 5, ANA positivity by IFAs (IFA1 95.2%; IFA2 98.9%) remained high, while there was a decrease in ELISA positivity (91.3%, p<0.001). Overall, there was >91% agreement in ANA positivity at all time points and ≥71% agreement in IFA patterns between IFA1 and IFA2. Conclusion: In recent-onset SLE, three ANA assays demonstrated commutability with a high proportion of positivity and titres or AU. However, over 5 years follow-up, there was modest variation in ANA assay performance. In clinical situations where the SLE diagnosis is being considered, a negative test by either the ELISA or HEp-2 IFA may require reflex testing.